Soluble magnesium alloy and preparation method and application thereof
By adding Cr and other microalloying elements to magnesium alloys to form AlCr and AlMgCr phases, the problems of low dissolution rate and high preparation cost of soluble magnesium alloys are solved. This enables rapid dissolution in chloride-containing aqueous solutions and improves mechanical properties, making it suitable for soluble components in shale oil and gas extraction.
Patent Information
- Application Number
- CN202511337564.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-18
- Publication Date
- 2025-12-19
AI Technical Summary
Existing soluble magnesium alloys have low dissolution rates and high preparation costs. In particular, the Mg17Al12 phase inhibits the dissolution rate of magnesium alloys in chloride-containing aqueous solutions, hindering their cost reduction process.
By adding Cr to magnesium alloys to form AlCr and/or AlMgCr phases, dissolution is promoted by utilizing the galvanic corrosion effect. The mechanical properties and solubility of the material are improved by adding Zn, Ca, Sn, Si and other elements. The alloy is prepared by using an Al-Cr master alloy and an inert atmosphere protection smelting process.
This method enables the rapid dissolution of magnesium alloys in chloride-containing aqueous solutions, improving the mechanical properties of the material and reducing preparation costs. It is suitable for soluble components in shale oil and gas extraction and has good prospects for industrial application.
Smart Images

Figure CN121161111A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the technical field of soluble magnesium alloy, and particularly relates to a soluble magnesium alloy and a preparation method and application thereof. BACKGROUND
[0002] The statements herein are provided only to complement the background of the present application and are not necessarily indicative of the prior art.
[0003] Soluble metal materials are widely used in shale oil and gas horizontal well staged fracturing exploitation. The temporary plugging balls and bridge plugs prepared from the soluble metal materials can be naturally dissolved in underground water environment, so that artificial removal is not needed, efficiency is improved, and cost is reduced. Magnesium alloy is an ideal soluble metal material due to its small density, high specific strength and specific stiffness, and low standard electrode potential.
[0004] Currently, soluble magnesium alloy is usually prepared by melting pure metal and intermediate alloy, which has high cost. Soluble magnesium alloy is a one-time consumable material and cannot be reused, so reducing the material cost is a key direction for commercial application.
[0005] Commercial magnesium alloy materials can be recycled at a relatively low price, and the use of the recycled commercial magnesium alloy materials can reduce the material cost. Commercial magnesium alloy includes Mg-Al series, Mg-Zn series, and Mg-RE series. Among them, Mg-Al series alloy is the most common and largest amount of brand, because the addition of Al improves the flowability of the alloy during casting, and the Mg 17 Al 12 phase formed can balance the strength and corrosion resistance. However, the Mg 17 Al 12 phase will inhibit or slow down the dissolution rate of magnesium alloy in a water solution containing chloride ions, which is not conducive to the preparation of soluble magnesium alloy and hinders the low-cost process of soluble magnesium alloy to some extent. SUMMARY
[0006] The present application aims to solve the problems of low dissolution rate and high preparation cost of the existing aluminum-containing magnesium alloy, and provides a soluble magnesium alloy and a preparation method and application thereof. The soluble magnesium alloy material contains a large amount of Al element and has high strength, and can be quickly dissolved in a water solution containing chloride ions.
[0007] In order to achieve the above-mentioned purpose, the present application is realized by the following technical scheme: In a first aspect, the present application provides a soluble magnesium alloy, which has a composition of Mg a Al b Cr c X d, 0.001 wt.% < b < 15 wt.%; 0.001 wt.% < c < 2 wt.%; 0.001 wt.% < d < 20 wt.%; and a + b + c + d = 100%; X is selected from at least one of Zn, Ca, Sn, Si, Li, Mn, Zr, Sc, Gd, Y, Nd, Ce, Sm, Er, Yb, Cu, Ni, Co, Fe or carbon-based powder materials.
[0008] In a second aspect, the present invention provides a method for preparing the soluble magnesium alloy, comprising the following steps: Weigh pure Mg, Al source, Cr source and X source in proportion. The Cr source is an Al-Cr master alloy. Melt each component under the protection of an inert atmosphere and cast it into an ingot. Perform homogenization heat treatment on the obtained ingot to obtain a soluble magnesium alloy.
[0009] In a third aspect of the present invention, there is provided an application of the above soluble magnesium alloy in the preparation of soluble components for shale oil and gas exploitation.
[0010] The beneficial effects obtained by one or more of the above embodiments of the present invention are as follows: (1) Through the microalloying of Cr in the present invention, the morphology of the Mg 17 Al 12 phase in the Mg-Al alloy is regulated, avoiding the protective effect of the network-like MgAl phase on the magnesium alloy matrix. Utilizing the galvanic corrosion effect of the AlCr phase and / or the AlMgCr phase, the rapid dissolution of the magnesium alloy in an aqueous solution containing chloride ions is promoted. The dissolution rate of the soluble magnesium alloy prepared in the present invention in a 3% KCl solution at room temperature is not less than 1 mg cm -2 h -1 . In addition, the high-melting-point AlCr phase and / or AlMgCr phase refine the grains of the soluble magnesium alloy through heterogeneous nucleation, improving the mechanical properties of the material.
[0011] (2) The melting point of Cr is about 1907 °C, and it is difficult to add during the melting process of the magnesium alloy. According to the Mg-Cr binary phase diagram, Mg and Cr do not form a second phase, and there is no Mg-Cr master alloy available in the market. In the present invention, by using an Al-Cr master alloy, the morphology of the MgAl phase in the magnesium-aluminum alloy is regulated to achieve the purpose of improving strength and dissolution performance. By preparing the soluble magnesium alloy in this way, recycled magnesium alloys with a relatively high aluminum content can be used as raw materials. The recycled materials are cheap, and the price of the Al-Cr master alloy is also not high. The entire process flow is easy to operate and is suitable for industrial production, with good application prospects.
[0012] (3) The application can add one or more of Zn, Ca, Sn, Si, Li, Mn, Zr, Sc, Gd, Y, Nd, Ce, Sm, Er, Yb, Cu, Ni, Co, Fe and other elements and carbon-based powder materials, further improving the mechanical properties and dissolution properties of the material. These elements can be added by pure metal, intermediate alloy, ball milling and other methods, or by recycling materials. This makes the composition selection range of the recycled materials more extensive and facilitates industrial production.
[0013] Mg a Al b Cr c X d The alloy is a soluble magnesium alloy and a preparation method thereof, wherein X is one or more of Zn, Ca, Sn, Si, Li, Mn, Zr, Sc, Gd, Y, Nd, Ce, Sm, Er, Yb, Cu, Ni, Co, Fe and other elements and carbon-based powder materials. The material avoids the protective effect of the magnesium-aluminum phase on the magnesium alloy substrate in a chloride-containing aqueous solution, and promotes the dissolution of the material through the galvanic corrosion effect of the aluminum-chromium phase or the aluminum-magnesium-chromium phase. The magnesium alloy can be prepared by casting, heat treatment, plastic forming and powder metallurgy processes, and has good mechanical properties and room temperature dissolution properties. The material has low cost, is easy to industrialize and has good application prospects. BRIEF DESCRIPTION OF DRAWINGS
[0014] The drawings accompanying the specification of the application form part of the specification and serve to further illustrate the application. The illustrative embodiments of the application and their description serve to explain the application without imposing undue limitation on the application.
[0015] Figure 1 is the microstructure of the as-cast Mg-9.0wt.%Al-0.8wt.%Cr-1.0wt.%Zn soluble magnesium alloy of Example 1.
[0016] Figure 2 is the microstructure of the as-extruded Mg-9.0wt.%Al-0.5wt.%Cr-1.0wt.%Zn-1.0wt%Cu-0.2wt%Ni soluble magnesium alloy of Example 3. DETAILED DESCRIPTION
[0017] It should be noted that the following detailed description is exemplary and is intended to provide further explanation of the application. Unless otherwise indicated, all technical and scientific terms used in the present application have the same meaning as generally understood by those skilled in the art to which the present application belongs.
[0018] In a first aspect, the present application provides a soluble magnesium alloy, which has a composition of Mg a Al b Crc X d 0.001wt.% < b < 15wt.%; 0.001wt.% < c < 2wt.%; 0.001wt.% < d < 20wt.%; and a+b+c+d=100%; X is selected from at least one of Zn, Ca, Sn, Si, Li, Mn, Zr, Sc, Gd, Y, Nd, Ce, Sm, Er, Yb, Cu, Ni, Co, Fe or carbon-based powder material.
[0019] The soluble magnesium alloy provided by the application can be prepared into a soluble material and a tool through processes such as casting, heat treatment, plastic forming and powder metallurgy.
[0020] The soluble magnesium alloy material provided by the application has good mechanical properties and can be dissolved at a relatively fast rate in a water solution containing chloride ions (such as a 3% KCl water solution).
[0021] The soluble magnesium alloy provided by the application, by adding Cr elements, regulates the distribution of Al elements and the phase composition of the structure, forms AlCr phases and / or AlMgCr phases with high melting points distributed at grain boundaries, refines the grains through a heterogeneous nucleation mechanism during the casting process of the soluble magnesium alloy, and improves the mechanical properties. 17 Al 12 Compared with the Mg 17 Al 12 phase, the electrode potential of the second phase containing Cr is higher, the continuous or semi-continuous distribution of Mg 17 Al 12 phase is destroyed through a micro-electric couple corrosion effect in the water solution, the protection of the magnesium matrix is realized, and a relatively fast dissolution rate is achieved.
[0022] The addition of one or more of Zn, Ca, Sn, Si, Li, Mn, Zr, Sc, Gd, Y, Nd, Ce, Sm, Er, Yb, Cu, Ni, Co, Fe and carbon-based powder material in the alloy can improve the mechanical or dissolution properties of the material. Among them, Zn, Sn, Si, Li, Gd, Y, Sm, Er, Yb and other elements can increase the strength of the magnesium alloy through solid solution strengthening or precipitation strengthening; Ca, Mn, Zr, Sc, Nd, Ce and other elements can refine the microstructure, thereby improving the strength and plasticity of the material; Cu, Ni, Co and other elements can form a second phase with high electrode potential with Mg, and further improve the dissolution rate of the material through the galvanic corrosion mechanism. Fe or carbon-based powder material can refine the magnesium alloy grains through heterogeneous nucleation, improve the mechanical properties of the material, and on the other hand, can be used as a material cathode phase to accelerate the dissolution of the magnesium alloy in the water solution containing chloride ions through galvanic corrosion.
[0023] In some embodiments, the carbon-based powder material is selected from carbon nanotubes, graphene or graphite.
[0024] Preferably, the carbon-based powder material is graphite.
[0025] In some embodiments, in the soluble magnesium alloy, 2.5wt.% < b < 9.5wt.%; 0.25wt.% < c < 3.0wt.%; 0.3wt.% < d < 3.0wt.%; and a + b + c + d = 100%.
[0026] Preferably, in the soluble magnesium alloy, 5wt.% < b < 9.5wt.%; 0.5wt.% < c < 1.0wt.%; 0.8wt.% < d < 3.0wt.%; and a + b + c + d = 100%.
[0027] In some embodiments, the specific composition of the soluble magnesium alloy is: Al 5-9.5%, Cr 0.5-1%, Zn 0.8-3%, the balance being Mg element, % being the mass percentage.
[0028] In some embodiments, the specific composition of the soluble magnesium alloy is: Al 5-9.5%, Cr 0.5-1%, Zn 0.8-2%, Cu 0.8-2%, Ni 0.8-2%, the balance being Mg element, % being the mass percentage.
[0029] In some embodiments, the specific composition of the soluble magnesium alloy is: Al 5-9.5%, Cr 0.5-1%, Zn 0.8-3%, graphite powder 0.5-3%, the balance being Mg element.
[0030] In a second aspect, the present application provides a preparation method of the soluble magnesium alloy, comprising the following steps: The pure Mg, Al source, Cr source and X source are weighed according to the proportion, the Cr source is Al-Cr intermediate alloy, each component is smelted under the protection of inert atmosphere, and is cast into an ingot; The obtained ingot is subjected to homogenization heat treatment to obtain the soluble magnesium alloy.
[0031] The present application controls the Mg 17 Al 12 phase morphology, avoids the protective effect of the network phase MgAl phase on the magnesium alloy substrate. The galvanic corrosion effect of the AlCr phase and / or the AlMgCr phase promotes the rapid dissolution of the magnesium alloy in the aqueous solution containing chloride ions.
[0032] In some embodiments, the Al source is pure Al or Mg-Al alloy.
[0033] In some embodiments, the X source is Mg-X intermediate alloy, when X is Fe, the iron source is pure iron powder.
[0034] In some embodiments, the smelting and casting into ingots method is as follows: after mixing the raw materials evenly, smelting under the protection of a mixed gas of CO2 and SF6 at 720-760℃, holding for 40-60min, refining and stirring for 5-10min; heating to 740-780℃ and standing for 20-40min, and pouring into ingots at 680-700℃.
[0035] Preferably, the volume ratio of CO2 to SF6 in the mixed gas of CO2 and SF6 is 100-200:1.
[0036] The mixed gas of CO2 and SF6 provides an inert protective atmosphere during the smelting of the magnesium alloy, prevents the oxidation of the magnesium alloy with oxygen in the air at high temperature, and ensures the stability and purity of the alloy composition. Among them, SF6 can form a protective film on the surface of the magnesium liquid, further inhibiting oxidation, while CO2 acts as a diluent gas to adjust the protection effect, and the two work together to achieve the anti-oxidation protection of the smelting process.
[0037] In some embodiments, the temperature of the homogenization heat treatment is 400-520℃, and the time is 1-96h.
[0038] Preferably, the cooling method after homogenization heat treatment is air cooling or water cooling.
[0039] In some embodiments, the method further comprises the step of plastic forming the prepared soluble magnesium alloy.
[0040] Preferably, the temperature of the plastic forming is 250-520℃, and the forming rate is 0.01-10m / min.
[0041] Preferably, the plastic forming method is hot extrusion, rolling or forging.
[0042] Preferably, the method further comprises the step of aging treatment of the plastic formed soluble magnesium alloy.
[0043] Further preferably, the temperature of the aging treatment is 100-300℃, and the time is 1-200h.
[0044] In some embodiments, when the X source is Fe powder and / or carbon-based powder, the X source is ball milled with Mg powder or Al powder, and then added in the form of a refining agent 0-5min before casting or during casting. The density of carbon-based powder is less than that of magnesium alloy, and the density of Fe powder is greater than that of magnesium alloy. If added during smelting, the one with lower density will float to the surface of the magnesium alloy liquid, and the one with higher density will sink to the bottom of the crucible, ultimately resulting in uncontrollable amount of addition to the magnesium alloy. The refining agent is generally added before pouring, so that the amount of addition is controllable.
[0045] In a third aspect, the present application provides use of the soluble magnesium alloy as described above in the preparation of a soluble component for shale oil and gas extraction.
[0046] The present application will be further described in conjunction with specific examples. It should be pointed out that the specific examples are illustrative of the present application rather than limiting.
[0047] Example 1 - Soluble magnesium alloy (as-cast) A soluble magnesium alloy, which is a Mg-Al-Cr-Zn alloy, is composed of the following elements in mass percentage: Al 9.0%, Cr 0.8%, Zn 1.0%, and the rest is Mg element.
[0048] Preparation process: according to the above alloy element ratio, take pure Mg, pure Al, pure Zn, and Al-30% Cr intermediate alloy (commercially available); under the protection of CO2+SF6 mixed gas (volume ratio of 100:1), melt pure Mg at 740℃, then add pure Al, pure Zn, and Al-Cr intermediate alloy in sequence; at 740℃, keep for 50 min, refine and stir for 10 min, and then increase the temperature to 760℃ and keep for 30 min; pour into a soluble magnesium alloy ingot at 700℃.
[0049] Example 2 - Soluble magnesium alloy (extruded state) The ingot of Example 1 is kept at 420℃ for 24 h and air-cooled, then peeled and processed into an extrusion billet; using an extrusion machine, extrude into a magnesium alloy rod under the conditions of an extrusion temperature of 400℃, an extrusion ratio of 60, and an extrusion speed of 2 m / min.
[0050] Example 3 - Soluble magnesium alloy (extruded state) A soluble magnesium alloy, which is a Mg-Al-Cr-Zn-Cu-Ni alloy, is composed of the following elements in mass percentage: Al 9.0%, Cr 0.5%, Zn 1.0%, Cu 1.0%, Ni 0.2%, and the rest is Mg element.
[0051] Preparation process: according to the above alloy element ratio, take pure Mg, pure Al, pure Zn, Al-30% Cr intermediate alloy, pure Cu, and Mg-Ni intermediate alloy; under the protection of CO2+SF6 mixed gas (volume ratio of 100:1), melt pure Mg at 740℃, then add pure Al, pure Zn, Al-Cr intermediate alloy, pure Cu, and Mg-Ni intermediate alloy in sequence; at 760℃, keep for 40~60 min, refine and stir for 5~10 min, increase the temperature to 760℃ and keep for 30 min; pour into a soluble magnesium alloy ingot at 690℃.
[0052] The ingot is cooled at 420°C for 24 hours, air-cooled, then peeled and processed into an extrusion blank. The extrusion blank is extruded into a magnesium alloy rod at an extrusion temperature of 400°C, an extrusion ratio of 15, and an extrusion speed of 3 m / min.
[0053] Example 4 - Soluble magnesium alloy (as-cast) A soluble magnesium alloy, which is a Mg-Al-Cr-X alloy, is composed of the following elements in mass percentage: Al 9.0%, Cr 0.8%, Zn 1.0%, graphite powder 0.5%, and the rest is Mg element.
[0054] Preparation process: according to the above alloy element ratio, pure Mg, pure Al, pure Zn, Al-30% Cr intermediate alloy, and graphite powder are weighed. The graphite powder and pure aluminum (mass ratio 1:1) are ball milled to form an intermediate powder.
[0055] The pure Mg is melted at 740°C under the protection of CO2+SF6 mixed gas (volume ratio 100:1), and then pure Al, pure Zn, and Al-Cr intermediate alloy are sequentially added. At 740°C, the alloy is kept for 50 min, refined and stirred for 10 min, heated to 760°C and kept for 30 min.
[0056] The temperature is lowered to 700°C, the mixture of graphite powder and pure aluminum is added, stirred for 1 min, and poured into a soluble magnesium alloy ingot.
[0057] Comparative Example 1 A magnesium alloy, which is a Mg-Al-Zn alloy, is composed of the following elements in mass percentage: Al 9.0%, Zn 1.0%, and the rest is Mg element.
[0058] Preparation process: according to the above alloy element ratio, pure Mg, pure Al, and pure Zn are weighed. The pure Mg is melted at 740°C under the protection of CO2+SF6 mixed gas (volume ratio 100:1), and then pure Al and pure Zn are sequentially added. At 740°C, the alloy is kept for 50 min, refined and stirred for 10 min, heated to 760°C and kept for 30 min. The alloy is poured into a soluble magnesium alloy ingot at 700°C.
[0059] Comparative Example 2 The ingot of Comparative Example 1 is cooled at 420°C for 24 hours, air-cooled, then peeled and processed into an extrusion blank. The extrusion blank is extruded into a magnesium alloy rod at an extrusion temperature of 400°C, an extrusion ratio of 60, and an extrusion speed of 2 m / min.
[0060] Comparative Example 3 A soluble magnesium alloy was prepared according to the same method as in Example 3, except for the alloy composition. The alloy was a Mg-Al-Zn-Cu-Ni alloy composed of the following elements in mass percentage: Al 9.0%, Zn 1.0%, Cu 1.0%, Ni 0.2%, and the rest was Mg element.
[0061] Comparative Example 4 A soluble magnesium alloy was prepared according to the same method as in Example 3, except for the alloy composition. The alloy was a Mg-Al-Zn-Cu-Ni alloy composed of the following elements in mass percentage: Al 9.0%, Zn 1.0%, Cu 1.0%, Ni 0.2%, and the rest was Mg element.
[0062] Preparation process: according to the above alloy element ratio, pure Mg, pure Al, pure Zn, Al-Cr intermediate alloy and graphite powder were weighed; under the protection of CO2+SF6 mixed gas (volume ratio of 100:1), pure Mg was melted at 740°C, and then pure Al, pure Zn, Al-30%Cr intermediate alloy and graphite powder were added in sequence; at 740°C, the alloy was kept for 50 min, refined and stirred for 10 min, and then heated to 760°C and kept for 30 min. The soluble magnesium alloy ingot was poured at 700°C.
[0063] Table 1 shows the mechanical properties and dissolution performance of the magnesium alloys in Examples 1-4 and Comparative Examples 1-4. The mechanical property test method is in accordance with GB T 228.1-2021; the dissolution performance is the test result in a 3% KCl aqueous solution at room temperature.
[0064] Table 1 Room temperature mechanical properties and dissolution performance of magnesium alloys
[0065] From the test performance results, the following characteristics can be found: (1) The tensile strength of the as-cast soluble magnesium alloy in Example 1 is 258 MPa, the yield strength is 180 MPa, and the elongation is 8%. Compared with the magnesium alloy without Cr (Comparative Example 1), the comprehensive mechanical properties are improved to a large extent. More importantly, the dissolution rate has changed significantly - from slow corrosion to faster dissolution. This is because AlCr phase and / or AlMgCr phase are generated in the microstructure Figure 1 ), which destroys the protective effect of Mg 17 Al 12 phase on the magnesium matrix.
[0066] (2) The extruded soluble magnesium alloy in Example 2 added Cr element, its strength and dissolution rate are also significantly improved than Comparative Example 2.
[0067] (3) The soluble magnesium alloy of Example 3 and Comparative Example 3 both added appropriate amounts of Cu and Ni elements, and the plasticity and solubility were also improved. This shows that the newly formed AlCr phase and / or AlMgCr phase, on the one hand, improves the microstructure of the material, and, like the Mg2Cu phase, promotes the dissolution of the magnesium alloy in the aqueous solution containing chloride ions through micro-galvanic corrosion.
[0068] (4) After adding appropriate amounts of graphite powder in Example 4, the strength and dissolution rate are both improved compared with Example 1. This is because the graphite powder plays a heterogeneous nucleation effect and a micro-galvanic corrosion effect. Compared with Example 4, the strength and dissolution rate of the material of Comparative Example 4 are relatively low. This shows that the addition of graphite powder in a conventional manner has no obvious effect on the strength and dissolution rate of the material (comparing Example 1).
[0069] In summary, the present application provides a soluble magnesium alloy material, which, after adding Cr elements, has good mechanical properties and solubility of the Al-containing soluble magnesium alloy, and can meet the performance requirements of the soluble metal material parts related to shale oil and gas development.
[0070] The above only describes the preferred embodiments of the present application and is not intended to limit the present application. For those skilled in the art, the present application can have various modifications and changes. Any modification, equivalent replacement, improvement, etc. within the spirit and principles of the present application shall be included in the protection scope of the present application.
Claims
1. A soluble magnesium alloy characterised in that: Mg a Al b Cr c X d 0.001 wt.% < b < 15 wt.%; 0.001 wt.% < c < 2 wt.%; 0.001 wt.% < d < 20 wt.%; and a + b + c + d = 100%; X is selected from at least one of Zn, Ca, Sn, Si, Li, Mn, Zr, Sc, Gd, Y, Nd, Ce, Sm, Er, Yb, Cu, Ni, Co, Fe or carbon-based powder material.
2. The soluble magnesium alloy of claim 1, wherein: The carbon-based powder material is selected from carbon nanotubes, graphene or graphite; Preferably, the carbon-based powder material is graphite.
3. The soluble magnesium alloy of claim 1, wherein: In the soluble magnesium alloy, 2.5wt.% < b < 9.5wt.%; 0.25wt.% < c < 3.0wt.%; 0.3wt.% < d < 3.0wt.%; and a + b + c + d = 100%; Preferably, in the soluble magnesium alloy, 5wt.% < b < 9.5wt.%; 0.5wt.% < c < 1.0wt.%; 0.8wt.% < d < 3.0wt.%; and a + b + c + d = 100%.
4. The soluble magnesium alloy of claim 1, wherein: The specific composition of the soluble magnesium alloy is: Al 5-9.5%, Cr 0.5-1%, Zn 0.8-3%, and the balance is Mg element, % is mass percent; Or, the specific composition of the soluble magnesium alloy is: Al 5-9.5%, Cr 0.5-1%, Zn 0.8-2%, Cu 0.8-2%, Ni 0.8-2%, and the balance is Mg element, % is mass percent; Or, the specific composition of the soluble magnesium alloy is: Al 5-9.5%, Cr 0.5-1%, Zn 0.8-3%, graphite powder 0.5-3%, and the balance is Mg element.
5. A method of producing the soluble magnesium alloy according to any one of claims 1 to 4, characterized in that: The method comprises the following steps: The pure Mg, Al source, Cr source and X source are weighed according to the proportion, the Cr source is Al-Cr intermediate alloy, and each component is melted and cast into an ingot under the protection of an inert atmosphere; The obtained ingot is subjected to homogenization heat treatment to obtain a soluble magnesium alloy.
6. The method of producing a soluble magnesium alloy according to claim 5, characterized by: The Al source is pure Al or Mg-Al alloy.
7. The method of producing a soluble magnesium alloy according to claim 5, characterized by: The X source is Mg-X intermediate alloy, and when X is Fe, the iron source is pure iron powder.
8. The method of producing a soluble magnesium alloy according to claim 5, characterized by: The method for melting and casting into an ingot is that after each raw material is uniformly mixed, melting is carried out at 720-760℃ under the protection of CO2 and SF6 mixed gas, heat preservation is carried out for 40-60min, refining and stirring are carried out for 5-10min; the temperature is increased to 740-780℃ and static is carried out for 20-40min, and the ingot is poured at 680-700℃; Preferably, in the CO2 and SF6 mixed gas, the volume ratio of CO2 to SF6 is 100-200:1; Or, the temperature of the homogenization heat treatment is 400-520℃, and the time is 1-96h; Preferably, the cooling mode after the homogenization heat treatment is air cooling or water cooling.
9. The method of producing a soluble magnesium alloy according to claim 5, characterized by: The method further comprises the step of plastic forming the prepared soluble magnesium alloy; Preferably, the temperature of the plastic forming is 250-520℃, and the forming rate is 0.01-10m / min; Preferably, the plastic forming mode is hot extrusion, rolling or forging; Preferably, the method further comprises the step of aging treatment of the plastic formed soluble magnesium alloy. Preferably, the temperature of the aging treatment is 100-300℃, and the time is 1-200h; or, when the X source is Fe powder and / or carbon-based powder, the X source is ball-milled with Mg powder or Al powder, and the refining agent is added in the form of a refining agent 0-5 minutes before casting or during casting.
10. Use of the soluble magnesium alloy according to any one of claims 1 to 4 for the production of soluble components for the exploitation of shale oil and gas.